(untitled) (Publicaciones en Ciencias y Tecnología, 2008)
In the last years the use of movable devices has been increased, the cellular telephones for example, they have stopped being only instruments of transmission of voice to become apparatuses able to process and to transmit information. The development of applications for these new devices must consider the peculiarities of such, the limitations as far as the interface of the client, execution of tasks, interaction of the data among others. Purpose of this work is to explain why to use the mediator pattern like a possible solution to the problem of the dynamic interfaces being implemented it through the movable agents, also to incorporate a quality model to evaluate platforms adapted for this work, The selection of the parameters that define the evaluation instrument is of vital importance for this, finally the solution is applied to a case of study in the dominion of the movable commerce.